Selective Aerobic Oxidation of 5‐HMF into 2, 5‐Furandicarboxylic Acid with Pt Catalysts Supported on TiO2‐ and ZrO2‐Based Supports. Issue 7 (3rd March 2015) - Ait Rass, Hicham; Essayem, Nadine; Besson, Michèle
Abstract Pt catalysts prepared over different metallic oxide supports were investigated in the oxidation of 5‐hydroxymethylfurfural (HMF) to 2, 5‐furandicarboxylic acid (FDCA) in alkaline aqueous solutions with air, to examine the combined effect of the support and base addition. The base (nature and amount) played a significant role in the degradation or oxidation of HMF. Increasing amounts of the weak NaHCO3 base improved significantly the overall catalytic activity of Pt/TiO2 and Pt/ZrO2 by accelerating the oxidation steps, especially for the aldehyde group. This was highlighted by a proposed kinetic model that gave very good concentration–time fittings. Moreover, the promotion of the catalyst with bismuth yielded a PtBi/TiO2 catalytic system with improved activity and stability. Y2O3 and La2O3ZrO2‐supported catalysts exhibited lower activity than Pt/ZrO2, which suggests no cooperative effect of the weakly basic properties introduced and the homogeneous base. Quantitative oxidation of HMF (0.1 M) and high yields of FDCA (>99 %) were obtained in less than 5 h by using an HMF/Pt molar ratio of 100 and Na2CO3 as a weak base over PtBi/TiO2 (Bi/Pt=0.22).